Drivers of Wealth Inequality in Euro-Area Countries - Sebastian Leitner (The Vienna Institute for International Economic Studies (wiiw), 2016)
Abstract This paper investigates the sources of inequality in household gross and net wealth across eight euro-area countries applying the Shapley value approach to decomposition. The research draws on micro data from the Eurosystem Household Finance and Consumption Survey 2010. Dispersion in bequests and inter vivos transfers obtained by households are found to have a remarkable effect on wealth inequality that is stronger than the one of income differences. In Austria, Germany and Cyprus the contribution of real and financial assets inherited or received as gifts to gross and net wealth inequality attains about 40%. Nevertheless, also the distribution of household characteristics (age, education, size, number of adults and children in the household, marital status) within countries shapes the observed wealth dispersion.
Keywords: D31; D63; O52; O57; 330; inequality; wealth distribution; decomposition analysis; inheritance; inter vivos transfers; income distribution; Europe